INTERNATIONAL ACADEMIC PROGRAM 2023 UNU SURAKARTA AT THE INDONESIAN SCHOOL KUALA LUMPUR MALAYSIA - Fachrurizal Bachrul Ulum; Abid Nurhuda; Syukron Ni’am; Umi Septina Anggraheni; Yulita Putri; Khoirun Nisa Nur’Aini; Reza Bagus Anugerah; Murjazin Murjazin (Jurnal Abdi Nusa, 2023)
International Academic Program in 2023 is an activity held by Nahdlatul 'Ulama University (UNU) Surakarta to increase the academic capacity of its students. And one of them is by visiting the Kuala Lumpur Malaysia Indonesian School (SIKL). So the purpose of this study is to describe this. The method used is field qualitative with data collection through observation, interviews, and outreach, and finally documentation in the implementation of activities. After collecting the data, it will be analyzed and concluded. The results showed that the International Academic Program 2023 UNU Surakarta at the Indonesian School of Kuala Lumpur Malaysia included an introduction to religious education for students at school, socialization and introduction to academic culture, a cooperation agreement between UNU Surakarta and SIKL, implementation of student microteaching for class X IPS and IPA students and finally a group photo as a memento so that it has an impact on the competence of UNU Surakarta students both personally, socially, professionally and pedagogically.